Comparison of the Kinematic Pattern of Knee Joint Flexion in Healthy and Genu Valgum and Genu Varum Children During Jumping - Hamed Jalalvand; Ali Fatahi; Zahra Entezari Khorasani (Biyumikānīk-i varzishī, 2022)
Objective Genu valgum and genu varum are considered as the most common abnormalities of the knee joint in the lower extremity. Identifying of the mentioned abnormalities in the early stages of life can prevent the occurrence of later problems in the physical condition of a person's life. Therefore, the aim of the present study was to compare the kinematic pattern of knee joint flexion in healthy children and genu valgum and genu varum children during jumping. Methods This study, 45 students in three groups (15 genu varum, 15 genu valgum and 15 healthy participated in the present study. Students performed long jump skills in front of a camcorder and measured information about the knee joint in three phases: take off, flight, and landing, using KINOVEA software. Data normality was investigated using Kolmogorov-Smirnov test and Mann- Whitney as well as kruskal-wallis nonparametric tests were employed for future analysis (P<0.05). Results There was a significant difference between healthy genu valgum and genu varum groups at take-off phase. No significant difference was observed between all three groups in the two other phases. Conclusion In genu valgum and genu varum groups the quadriceps muscles are affected to create dynamic stability in the frontal and sagittal planes.